Perkembangan Moral Siswa-Siswi Kelas VIII dalam Ruang Lingkup Lingkungan Sekolah di SMPN 2 Pucuk Lamongan - Retno Dwi Agustin; Muhimmatul Hasanah (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2021)
Factors that influence adolescent development are internal and external. The environment in question is the social environment of peers from outside or friends in the association from within. The main factor that determines the attractiveness of interpersonal relationships among adolescents in general is the similarity in interests, values, opinions, and personality traits. Moral education taught to adolescents will greatly affect the character in the school environment. Parents must be willing to engage in conversation and encourage their children to talk about things related to values ​​that will make children have high moral thinking. The role of parents here is very important to always monitor the moral development that occurs in their children in the school environment. Moral development related to the daily life of students at the school environment level is very influential in the attitudes that occur in the lives of students so that there is a lack of student morals in the school environment and a lot of social ethics that deviate from the association of students. The findings in the research above, there are about moral development and the causal factors of moral development or often called the influence of the moral development of class VIII SMP Negeri 2 Pucuk Lamongan, both from external and internal environmental problems.